Phenotype Analysis of Fused in Sarcoma Mutations in Amyotrophic Lateral Sclerosis. (12th October 2022) - Grassano, Maurizio; Brodini, Giorgia; De Marco, Giovanni; Casale, Federico; Fuda, Giuseppe; Salamone, Paolina; Brunetti, Maura; Sbaiz, Luca; Gallone, Salvatore; Cugnasco, Paolo; Bombaci, Alessandro; Vasta, Rosario; et al.
Abstract : Background and Objectives: Pathogenic variations in fused in sarcoma (FUS) are among the most common genetic causes of amyotrophic lateral sclerosis (ALS) worldwide. They are supposedly characterized by a homogeneous pure motor phenotype with early-onset and short disease duration. However, a few FUS- mutated cases with a very late disease onset and slow progression have been reported. To analyze genotype-phenotype correlations and identify the prognostic factors in FUS -ALS cases. Methods: We identified and cross-sectionally analyzed 22 FUS -ALS patient histories from a single-center cohort of 2, 615 genetically tested patients and reviewed 289 previously published FUS -ALS cases. Survival analysis was performed by Kaplan-Meier survival curves, followed by the log-rank test and multivariate Cox analysis. Results: Survival of FUS -ALS is age-dependent: In our cohort, early-onset cases had a rapid disease progression and short survival ( p = 0.000003) while the outcome of FUS -mutated patients with mid-to-late onset did not differ from non– FUS -ALS patients ( p = 0.437). Meta-analysis of literature data confirmed this trend ( p = 0.00003). This survival pattern is not observed in other ALS-related genes in our series. We clustered FUS -ALS patients in 3 phenotypes: (1) axial ALS, with upper cervical and dropped-head onset in mid-to-late adulthood; (2) benign ALS, usually with a late-onset and slow disease progression; and (3) juvenile ALS, often with bulbar onset and preceded by learning disability or mild mental retardation. Those phenotypes arise from different mutations. Discussion: We observed specific genotype-phenotype correlations of FUS -ALS and identified age at onset as the most critical prognostic factor. Our results demonstrated that FUS mutations underlie a specific subtype of ALS and enable a careful stratification of newly diagnosed FUS -ALS cases for clinical course and potential therapeutic windows. This will be crucial in the light of incoming gene-specific therapy.